Akibat Hukum Dari Pembatalan Akta Jual Beli Tanah - Yunardi, Novita Putri; Raffles, Raffles; Yahya, Taufik (Universitas Batanghari Jambi, 2025)
The purpose of this study is to investigate what happens legally when a Sale and Purchase Agreement is cancelled.One of the most fundamental aspects of human existence is the ability to buy and sell land. In actuality, disagreements over land purchases and sales can lead to the SALE AND PURCHASE Deed being voided. Using both primary and secondary sources of information, this study employs a descriptive-analytical approach to its normative legal research. After a judge nullifies a sale and purchase deed, all circumstances are returned to how they were before the deal was subject to any legal proceedings. Any performance received by one party from another must be returned to the original sender. Furthermore, the Land Deed Official shall affix or include the Court Decision in the Notarial Deed Minute to document the cancellation. One party must apply to the National Land Agency to annul the land certificate if it has been transferred. Following the District Court's ruling, the National Land Agency will either cancel the certificate via the Administrative Court or strike out and substitute the owner's name.